Radical Target Setting and China's Great Famine. (25th October 2021) - Liu, Chang; Zhou, Li-An
Abstract: This article empirically examines the role of radical targets for grain yields in triggering China's Great Famine (1959–61), one of the largest man-made catastrophes in human history. Beginning in 1958, the Chinese central government assigned different targets for grain yields in most counties, based on their geographic location. All targets seemed unrealistically high. Using novel county-level data, combined with a spatial regression discontinuity strategy, we find evidence that these radical grain targets prompted excessive procurement and subsequent famine. Our estimates show that a one-standard deviation increase in grain yield targets led to an 18‰ higher death rate in 1960. This article sheds new light on the consequences of target-setting in an authoritarian regime without considering local contexts. ( JEL O21, N45, P26).